Acculturative status, age, and hypertension among African American women - Webb, Fern J.; Jones, Christina; Jones, Ross; Morga, Kristen; Bilello, Lori; Khubchandani, Jagdish (International Journal Of Community Medicine And Public Health, 2021)
Background: Understanding culture’s impact on hypertension (HTN) is important since its prevalence in African American women (AAW) in the United States is among the highest. It is therefore important to know if younger AAW have similar acculturation status as older AAW when developing culturally relevant interventions. The objective of this study was to examine the association between acculturation status and age, determining whether acculturation status and age are significantly associated with hypertension among AAW. Methods: Acculturation status, age, and HTN were analyzed using data from the listening to our voices study (LOVS), a population-based observational study of 294 AAW conducted throughout Florida. LOVS was promoted via African American women research assistants trained to inform and recruit AAW living in Ft. Lauderdale, Jacksonville, Miami, and Tampa. Results: Findings demonstrate that AAW held traditional values regardless of age. Moreover, AAW of younger ages had higher average acculturation scores compared with older AAW indicating stronger agreement with traditional values, practices and beliefs. Acculturation subscale scores were not associated with HTN. AAW with HTN scored higher on the traditional food subscale compared to AAW without HTN. Conclusions: These findings indicate the significance of considering the beliefs, values, and practices of AAW when developing health interventions. Health interventions developed should be tailored toward AAW of varying ages to incorporate activities relevant to their cultural beliefs, values and practices.